Co-movements of major Asian-Pacific and the United States equity markets : a Singapore dollar perspective. - Cheow, Hock Beng. (2009)
This paper investigates the lead/lag relationships among major the Asian-Pacific and United States equity markets from a Singapore investor's perspective. Using daily closing index data for the period from 4 January 1988 to 21 April 1994, we apply Granger Causality techniques to determine the degree and direction of causality between the Singapore and other major foreign equity markets.